Effects of Urethral Stricture on Allografts in Kidney Transplantation - (:unkn) unknown (ELSEVIER SCIENCE INC, 2015)
Background. Iatrogenic urethral stricture after renal transplantation is mostly seen after urethral manipulations. Early diagnosis and treatment are crucial for the safe continuity of the graft functions. In this study, the effect of urethral strictures on graft functions during the post-transplantation period was investigated. Methods. A total of 477 kidney transplantations were carried out from both live and cadaveric donors in our center from 2004 to 2014. Thirty-two patients who had insufficient data were excluded from the study. All the patients' urine cultures were negative before the surgery, and antibiotic prophylaxis were applied to all. Urethral catheters were taken out 4-7 days after transplantation. Double-J catheters were removed 6 weeks later. Internal urethrotomy and open urethroplasty surgeries were done for the patients who had urethral stricture. The results of creatinine, post-micturitional residual urine (PMR), International Prostate Symptom Score (IPSS), and uroflow examinations were evaluated. Results. Average preoperative creatinine and postoperative creatinine values were, respectively, 1.74 +/- 0.65 mg/dL (range, 0.83-3.03) and 1.24 +/- 0.57 mg/dL (range, 0.9-2.24). A meaningful improvement was observed in terms of preoperative and postoperative IPSS values. A significant difference was seen between preoperative and 6th-month postoperative PMR values: 192.6 +/- 57.2 mL and 36.7 +/- 17.4 mL, respectively. Conclusions. Urethral strictures in transplant patients may arise due to many factors, such as repetitive urethral catheterization and inflammation. Early diagnosis helps to have better results for the treatment of the kidney functions.
Keywords: ETIOLOGY